Manufacturing companies and financial performance :what is the role of intellectual capital, environmental performance and environmental cost? - Ahmad Gamal; Kustianing Sekar; Asep Iwa Soemantri (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of Intellectual Capital, environmental performance and environmental cost on financial performance in the manufacturing sector. Green accounting is measured by environmental cost and environmental performance which are independent variables in this study. While the company's performance is measured by financial performance as a proxy for ROA. This research was conducted on manufacturing companies that are PROPER participants and listed on the Indonesia Stock Exchange (IDX) for the period 2017 – 2019. This study uses multiple regression analysis with SPSS version 23 program. The sample in this study used purposive sampling method to obtain 36 samples of sector companies. manufacture. The results of this study indicate that Intellectual Capital has an effect on financial performance. Meanwhile, environmental performance and environmental cost have no effect on financial performance. Simultaneously Intellectual Capital, environmental performance and environmental cost affect financial performance.